2016
DOI: 10.1007/s00438-016-1267-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the early Hungarian conquerors inferred from mtDNA haplotypes and Y-chromosome haplogroups in a small cemetery

Abstract: We applied ancient DNA methods to shed light on the origin of ancient Hungarians and their relation to modern populations. Hungarians moved into the Carpathian Basin from the Eurasian Pontic steppes in the year 895 AD as a confederation of seven tribes, but their further origin remains obscure. Here, we present 17 mtDNA haplotypes and four Y-chromosome haplogroups, which portray the genetic composition of an entire small cemetery of the first generation Hungarians. Using novel algorithms to compare these mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 32 publications
6
64
0
2
Order By: Relevance
“…In the 15 samples of [9] the same haplogroups were assigned from NGS data in all cases, however only 8 haplotypes proved to be correct. In both studies the majority of deviations originated from undetected SNP-s in sequencing reactions of PCR fragments, but [7] also identified 3 SNP-s erroneously (lined through nucleotide positions in Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 15 samples of [9] the same haplogroups were assigned from NGS data in all cases, however only 8 haplotypes proved to be correct. In both studies the majority of deviations originated from undetected SNP-s in sequencing reactions of PCR fragments, but [7] also identified 3 SNP-s erroneously (lined through nucleotide positions in Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Bone powder remains of samples from the study of [9], were saved in the Department of Genetics, University of Szeged, and were reused to build NGS sequencing libraries.…”
Section: Methodsmentioning
confidence: 99%
“…Although mtDNA data can be informative, since as far as we know none of the above nomadic invasions were pure military expeditions in which raiding males took local women, but entire societies with both men and women migrated together 3 , however nomadic societies were patrilinealy organized, thus Y-chromosome data are expected to provide more relevant information about their structure and origin than mtDNA. So far 6 Ychromosome Hg-s have been published from the Conquerors; 12 which revealed the presence of N1a1-M46 (previously called Tat or N1c), in two out of 4 men, while 13 detected two R1b-U106 and two I2a-M170 Hg-s.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [14] showed the presence of N-Tat (M46) Y-chromosome marker (a major clade of the above mentioned N-L1034) in two of the Conqueror samples and one living Sekler, which was interpreted as a Finno-Ugric link. It is notable that in the latest studies [12,13] population genetic analysis also indicated considerable Central Asian affinity of the Conquerors. However all these studies applied low resolution, error prone PCR based aDNA methods [15] and high resolution Next Generation Sequencing (NGS) data from the Conquerors has not been available yet, though power of discrimination of the entire mitochondrial genome over the hypervariable regions (HVR) has been shown to be huge [16].…”
Section: Introductionmentioning
confidence: 97%
“…The genetic composition of the Conquerors was also analyzed in several ancient DNA (aDNA) studies [11][12][13] and indeed, all these detected significant presence of East Eurasian major mtDNA haplogroups (Hg-s), which are rare in modern Hungarians but are found in Uralic people. Another study [14] showed the presence of N-Tat (M46) Y-chromosome marker (a major clade of the above mentioned N-L1034) in two of the Conqueror samples and one living Sekler, which was interpreted as a Finno-Ugric link.…”
Section: Introductionmentioning
confidence: 99%